Widely untargeted metabolomic profiling unearths metabolites and pathways involved in leaf senescence and N remobilization in spring-cultivated wheat under different N regimes - Effah, Zechariah; Li, Lingling; Xie, Junhong; Karikari, Benjamin; Xu, Aixia; Wang, Linlin; Du, Changliang; Duku Boamah, Emmanuel; Adingo, Samuel; Zeng, Min (Frontiers in Plant Science, 2023)
More than half of the nutrition required for the formation of wheat grains is found in its flag leaves, which are important source organs. However, little is known about the metabolites and their biosynthetic pathways involved in leaf senescence and nitrogen (N) remobilization under varying N rates in spring wheat. Therefore, we applied widely untargeted metabolome profiling to identify metabolites and biosynthetic pathways that could be used in a wheat improvement programs to manipulate flag leaves senescence. Spring wheat (Dingxi 38) flag leaves were sampled from no (G1), low (G2), and high N (G3) regimes at three different stages: anthesis, grain filling, and end grain filling. Overall, 826 metabolites were detected: 107 flavonoids, 51 phenol lipids, 37 fatty Acyls, 37 organooxygen compounds, 31 steroids and steroid derivatives, 18 phenols, and several unknown compounds. A total of 28 and 23 metabolites were differentially accumulated in G1_vs_G2 and G1_vs_G3, respectively. Two anthocyanin biosynthetic-based metabolites (cyanidin 3-O-rutinoside and peonidin 3-O-glucoside) and two flavone and flavonol biosynthetic-based metabolites (rhoifolin and astragalin) accumulated higher under N limited conditions (G1 and G2) than in G3. The findings of this study lay the foundation for controlling the timing and pace of wheat leaf senescence and N remobilization.